2017
DOI: 10.1016/j.ijdevneu.2017.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Efficient neural differentiation of mouse pluripotent stem cells in a serum‐free medium and development of a novel strategy for enrichment of neural cells

Abstract: Pluripotent stem cells (PSCs) offer an excellent model to study neural development and function. Although various protocols have been developed to direct the differentiation of PSCs into desired neural cell types, many of them suffer from limitations including low efficiency, long duration of culture, and the use of expensive, labile, and undefined growth supplements. In this study, we achieved efficient differentiation of mouse PSCs to neural lineage, in the absence of exogenous molecules, by employing a seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…For embryoid body (EB) differentiation the original protocol was slightly adapted 58 . For neural differentiation: ESCs were seeded as a single cell suspension at a concentration of 100,000-200,000 cells/ml in ESC media containing FBS (as in the original protocol) or knockout serum replacement (KSR) 59 lacking hLIF and 2i on ultra-low attachment plates (Corning). After 4 days of culture all trans retinoic acid (ATRA) (Sigma) or the synthetic substitute EC23 (Abcam) was added to the media at a concentration of 0.5 μM.…”
Section: Methodsmentioning
confidence: 99%
“…For embryoid body (EB) differentiation the original protocol was slightly adapted 58 . For neural differentiation: ESCs were seeded as a single cell suspension at a concentration of 100,000-200,000 cells/ml in ESC media containing FBS (as in the original protocol) or knockout serum replacement (KSR) 59 lacking hLIF and 2i on ultra-low attachment plates (Corning). After 4 days of culture all trans retinoic acid (ATRA) (Sigma) or the synthetic substitute EC23 (Abcam) was added to the media at a concentration of 0.5 μM.…”
Section: Methodsmentioning
confidence: 99%
“…To obtain feeder-free ESCs, the ESCs were grown on a 0.1% gelatin-coated dish in 2i + LIF medium. For cell differentiation to neuronal and glial lineage cells, we integrated the differentiation protocols previously described [23,24]. First, the mouse ESCs were trypsinized to single cells and then replaced at 1 × 10 4 cells per well of an ultralow adhesion 96-well plate to quickly aggregate and form uniformly sized embryoid bodies in KSR medium (high glucose DMEM supplemented with 15% knockout serum replacement, 0.1 mM nonessential amino acids, 0.1 mM 2-mercaptoethanol, 2 mM Glutamine, 100 U/ml penicillin/streptomycin, and 10 μM SB431542).…”
Section: Methodsmentioning
confidence: 99%
“…Accumulating studies have showed that Lin28 regulates ESC proliferation and neurogenesis in vitro, but the underlying mechanism is not clear [14,15]. Here, we utilized previously described protocols to directly differentiate mouse ESCs to neurons and glias in vitro [23,24]. As shown in Figures 2(a) and 2(b), mESCs were trypsinized to single cells and cultured in an ultralow attachment 96-well plate to quickly aggregate and grow uniformly sized embryoid bodies (EBs) in KSR medium.…”
Section: Lin28a/b Induced Yap1 But Inhibited Lineage-specific Gene Expression In Mescsmentioning
confidence: 99%
“…For more than a couple of decades, we have been studying early mammalian development particularly with three dynamic developmental phenomena viz., (i) sperm hyper-activation involving molecular dissection of capacitation-associated sperm protein tyrosine phosphorylation changes critical for sperm fertilization (Ain et al, 1999;Mariappa et al, 2006;Seshagiri et al, 2007;Mariappa et al, 2010), (ii) cellular and molecular regulation of development and hatching of blastocysts (Seshagiri et al, 2003(Seshagiri et al, , 2009(Seshagiri et al, , 2016) and (3) establishment of blastocyst-derived embryonic stem cell (ESC) lines and the cell lineage-specification and functional differentiation (Verma et al, 2017). We established the first Indian EGFP-expressing transgenic green mouse (GU-2 and GU-3) lines (Singh et al, 2012) and subsequently, derived two PSC lines viz., the GS-2 ESC (Singh et al, 2012) and the N9 iPSC (Abbey et al, 2019) lines.…”
Section: Embryo Development and Functionmentioning
confidence: 99%